SIGNIFICANCE AND SCHEMES OF HYDROACCUMULATION POWER STATIONS IN ELECTRICAL POWER SYSTEMS - U.J.Kuvatov; O.O.Nazarov; I.O.Sattorov; S.I.Davranov (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Today, the world is paying special attention to the field of hydropower. Among them, small-capacity hydro accumulation power plants occupy the most important place. In this article, the importance of GAES in the energy system is considered.